Erythroderma: A clinico-etiological study of 58 cases in a tertiary hospital of North India - Shirazi, Nadia; Jindal, Rashmi; Jain, Akanksha; Yadav, Kanika; Ahmad, Sohaib (Asian Journal of Medical Sciences, 2015)
Background: Erythroderma (exfoliative dermatitis) is a cutaneous reaction pattern characterized by generalized erythema and scaling which can be seen in a wide range of cutaneous or systemic diseases. It is important to establish correct diagnosis whenever possible so that specific therapy may be initiated. The study was undertaken to evaluate the clinical profile and etiology of erythroderma and to correlate clinical diagnosis with histopathological findings. Methods: A retrospective study was done in the Department of Pathology. Fifty eight cases of erythroderma diagnosed clinically in the past 5 years were studied and their epidemiological, clinical, laboratory and histopathological findings were analyzed. Results: The mean age of presentation was 39.3 years and male to female ratio was 3:2. Apart from erythema and scaling that were present in all patients, pruritis (n=40,69%), edema (n=12,20.2%) and fever (n=11,19%) were the most common symptoms at presentation. The most common etiology of exfoliative dermatitis was drug reactions (n=19,32.7%) followed by atopic dermatitis (n=12,20.6%) and erythrodermic psoriasis (n=10,7.2%). Other causes were Mycosis Fungoides, Allergic/Air borne contact dermatitis, Lichen Planus, Pityriasis Rubra Pilaris. There was no significant contribution of laboratory data and all the patients were HIV negative. The best clinicopathological correlation (100%) was found in erythrodermic psoriasis and Mycosis Fungoides. Conclusion: Erythroderma often obscures the primary lesion. Clinicians should evaluate all cases of erythroderma by eliciting proper clinical history, taking biopsies and performing other ancillary haematological investigations. Hospitalization may be required as the disease carries risk of significant mortality. DOI: http://dx.doi.org/10.3126/ajms.v6i6.12265 Asian Journal of Medical Sciences Vol.6(6) 2015 20-24